A precise relationship among Buller's drop, ballistospore, and gill morphologies enables maximum packing of spores within gilled mushrooms. (4th March 2021) - Iapichino, Martina; Wang, Yen-Wen; Gentry, Savannah; Pringle, Anne; Seminara, Agnese
ABSTRACT: Basidiomycete fungi eject basidiospores using a surface tension catapult. A fluid drop forms at the base of each spore and, after reaching a critical size, coalesces with the spore and launches it from the gill surface. It has long been hypothesized that basidiomycete fungi pack the maximum number of spores into a minimal investment of biomass. Building on a nascent understanding of the physics underpinning the surface tension catapult, we modeled a spore's trajectory away from a basidium and demonstrated that to achieve maximum packing the size of the fluid drop, the size of the spore, and the distance between gills must be finely coordinated. To compare the model with data, we measured spore and gill morphologies from wild mushrooms and compared measurements with the model. The empirical data suggest that in order to pack the maximum number of spores into the least amount of biomass, the size of Buller's drop should be smaller but comparable to the spore size. Previously published data of Buller's drop and spore sizes support our hypothesis and also suggest a linear scaling between spore radius and Buller's drop radius. Morphological features of the surface tension catapult appear tightly regulated to enable maximum packing of spores. If mushrooms are maximally packed and Buller's drop radii scale linearly with spore radii, we predict that intergill distance should be proportional to spore radius to the power 3/2.